2014
DOI: 10.15361/1984-5529.2014v42n3p224-232
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento germinativo de sementes de cultivares de milho sob condições de hipoxia

Abstract: ResumoA diversidade genética existente no milho permite seu cultivo nos mais diversos ambientes. Contudo, o excesso de chuva, em regiões úmidas e quentes, logo após a semeadura, pode prejudicar a germinação por restringir o oxigênio ou causar danos embrionários provocados pela embebição demasiadamente rápida. Deste modo, este trabalho teve por objetivo verificar os efeitos de períodos de hipoxia na germinação de sementes de diferentes cultivares de milho. Foram utilizados três tipos de cultivares, sendo dois h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
1
7
0
1
Order By: Relevance
“…Hence, although there may have been a reduction in the percentage of normal seedlings, this reduction was not extremely negative. This corroborates the results obtained by Gazola et al (2014), who verified that variations in the periods of hypoxia (32 and 49 hours) were beneficial to the increase of the percentage of normal seedlings in the first germination count of maize seeds.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…Hence, although there may have been a reduction in the percentage of normal seedlings, this reduction was not extremely negative. This corroborates the results obtained by Gazola et al (2014), who verified that variations in the periods of hypoxia (32 and 49 hours) were beneficial to the increase of the percentage of normal seedlings in the first germination count of maize seeds.…”
supporting
confidence: 92%
“…Many studies have shown changes in germination percentage and in the initial morphophysiological characteristics of several species when subjected to hypoxia, including white oats (Rosa et al, 2015), beans (Custódio et al, 2002;Custódio et al, 2009;Pedó et al, 2017), maize (Dantas et al, 2000;Gazola et al, 2014), and soybean (Gazolla Neto et al, 2012). Moreover, the seed survival rate may show varietal differences after some flooding levels (Gazola et al, 2014;Pedó et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for both tests, the treatments that exceeded immersion in water were only KNO 3 at 4% and 2%. The deleterious effect of immersion in water on these variables may have been caused by hypoxia, which compromises cell metabolism and results in loss of the physiological potential and viability of the seeds (Gazola, Zucareli, & Camargo, 2014).…”
Section: Controlsmentioning
confidence: 99%
“…Assim, esses altos valores de precipitação pluvial ao longo dos ciclos podem ter interferido nas características morfológicas das plantas de milho, uma vez que o excesso de chuva pode ter ocasionado lixiviação de nutrientes como também falta de oxigênio livre para as plantas (Galon et al, 2010). Gazola et al (2014) e Moterle et al (2006) também observaram que o excesso de chuva pode prejudicar a germinação e as fases de desenvolvimento da cultura do milho, visto que impede a penetração do oxigênio e reduz todo o processo metabólico resultante, ocasionando perdas significativas na produtividade. Além disso, a alta sensibilidade da cultura em um período tão curto, associada à grande variabilidade na distribuição de chuvas durante a estação quente, faz do milho uma cultura altamente suscetível ao fator água.…”
Section: Híbridounclassified